Aulas pasaule - LU Vēstures muzejs (LU Muzejs, 2012)
Latvijas Universitātes Lielā aula, kas atrodas LU galvenajā ēkā Raiņa bulvārī 19, ir nozīmīga svinību vieta ne tikai LU, bet arī pašai Latvijai kopumā. To izmanto Dziesmu svētku koru kariem un citiem koncertiem, kā arī svinīgiem pasākumiem. LU Lielajā aulā ir notikušas arī starptautiskas un valstiska līmeņa konferences, kurās ir uzstājušies ārvalstu vadītāji un diplomāti. Virtuālā izstāde tapusi par godu LU Lielās aulas 75 gadu jubilejai.
The Great Aula of the University of Latvia, located in the main building of the University of Latvia, is an important place of celebration not only for the University of Latvia, but also for Latvia as a whole. It is used for the Song Festival Choir Wars and other concerts, as well as for festive events. The Great Aula has also hosted international and national conferences, where foreign leaders and diplomats have spoken. The virtual exhibition was created on the occasion of the 75th anniversary of the Great Aula of the University of Latvia.
Keywords: Research Subject Categories::TECHNOLOGY::Civil engineering and architecture::Architecture and architectural conservation and restoration::Architecture; Latvijas Universitāte; Lielā aula; Arhitektūra; Ernests Štālbergs; Kultūra un māksla; Augstākā izglītība; Tradīcijas; The University of Latvia; Great Aula; Architecture; Ernest Stalbergs; Culture and Arts; Higher Education; Traditions